Multidrug resistance in pathogenic Escherichia coli isolates from urinary tract infections in dogs, Spain - Abad-Fau, Ana; Sevilla, Eloisa; Oro, Ainara; Martín-Burriel, Inmaculada; Moreno, Bernardino; Morales, Mariano; Bolea, Rosa (Frontiers in Veterinary Science, 2024)
Escherichia coli (E. coli) is a pathogen frequently isolated in cases of urinary tract infections (UTIs) in both humans and dogs and evidence exists that dogs are reservoirs for human infections. In addition, E. coli is associated to increasing antimicrobial resistance rates. This study focuses on the analysis of antimicrobial resistance and the presence of selected virulence genes in E. coli isolates from a Spanish dog population suffering from UTI. This collection of isolates showed an extremely high level of phenotypic resistance to 1 st -3 rd generation cephalosporins, followed by penicillins, fluoroquinolones and amphenicols. Apart from that, 13.46% of them were considered extendedspectrum beta-lactamase producers. An alarmingly high percentage (71.15%) of multidrug resistant isolates were also detected. There was a good correlation between the antimicrobial resistance genes found and the phenotypic resistance expressed. Most of the isolates were classified as extraintestinal pathogenic E. coli, and two others harbored virulence factors related to diarrheagenic pathotypes. A significant relationship between low antibiotic resistance and high virulence factor carriage was found, but the mechanisms behind it are still poorly understood. The detection of high antimicrobial resistance rates to first-choice treatments highlights the need of constant antimicrobial resistance surveillance, as well as continuous revision of therapeutic guidelines for canine UTI to adapt them to changes in antimicrobial resistance patterns.